Applications of smartphone-based in improving self-management of non-communicable disease: Literature review - Rizkiyani Istifada; Muhammad Asnoer Laagu (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
Non-communicable diseases (NCDs) are one of the leading health problems that occur in the adult people. One strategy to improve self-management of NCDs during the COVID-19 pandemic is to use a smartphone-based application. This literature review is structured to describe applications smartphone-based to improve self-management of NCDs. The databases in e-resources included Wiley Online, ScienceDirect, and Cambridge Core from 2010-2021. A literature search resulted in 15 articles that focused on using applications as a medium for improving self-management of NCDs. Various studies have shown the benefits of the use of smartphone-based applications to improve self-management strategies, including (1) the application to count the physical activity score; (2) the self-management application to manage nutritional diets; (3) the application of pain evaluation; (4) the application of weight management, and (5) the application of self-disease management record. The existence of a smartphone-based application can reduce the limitations in the process of implementing and evaluating self-management of non-communicable diseases.